2018
DOI: 10.2478/logos-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Application of geostatistical analyst methods in discovering concealed gold and pathfinder elements as geochemical anomalies related to ore mineralisation

Abstract: The study area in the West Junggar Basin is known to be rich in hydrothermal gold deposits and occurrences, even though there has been minimum exploration in the area. It is here hypothesised that this area could host more gold deposits if mineral exploration methods were to be reinforced. This research is aimed at identifying geochemical anomalies of Au, and determining possible factors and conditions which facilitate the formation of anomalies by referring to As and Hg as gold pathfinders. Geostatistical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…XRD has been used to conclude that highly hydrated and water saturated environments contribute to the migration of Au within alluvia regimes and on hydrothermal mineral assemblages [7][8][9]. Multivariate statistical analysis and geostatistical methods have been applied to identify pathfinding elements [10][11]. Bayari et al [4] found that mineralized regolith profiles and mobility of elements (minerals) in the soil at the Bole-Nangoli gold belt in the north-eastern Ghana could mainly be attributed to amorphous mineral phases.…”
Section: Introductionmentioning
confidence: 99%
“…XRD has been used to conclude that highly hydrated and water saturated environments contribute to the migration of Au within alluvia regimes and on hydrothermal mineral assemblages [7][8][9]. Multivariate statistical analysis and geostatistical methods have been applied to identify pathfinding elements [10][11]. Bayari et al [4] found that mineralized regolith profiles and mobility of elements (minerals) in the soil at the Bole-Nangoli gold belt in the north-eastern Ghana could mainly be attributed to amorphous mineral phases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both multispectral and hyperspectral sensors play a greater role in mineral exploration studies as they can cover larger areas. Several studies [35,36] have demonstrated that geostatistical analysis techniques of bedrock and stream sediments were successful in determining the background and threshold values and identifying Au and pathfinder anomalies. In addition, the number of faults and folds, in particular their junctions, also help because those faults, fracture systems, and permeability together enhance an easier and faster flow of hydrothermal fluids towards the surface, which results in the formation of geochemical anomalies.…”
Section: Portable Techniques For Mineral Exploration Studiesmentioning
confidence: 99%
“…Several studies (e.g., Lindagato et al 2018) have demonstrated that geostatistical analysis techniques to bedrock and stream sediments were successful in determining the background and threshold values and identifying Au and pathfinder anomalies. In addition, the number of faults and folds, in particular their junctions also help because those faults, fracture systems and permeability together enhance an easier and faster flow of hydrothermal fluids towards the surface, which results in the formation of geochemical anomalies.…”
Section: Portable Techniques For Mineral Exploration Studiesmentioning
confidence: 99%